The Concept of Collaboration with 20th-Century Occupation Regimes in Lithuanian Public Opinion: Interpretations and Relevance - Šutinienė, Irena (Genocidas ir rezistencija, 2026)
Drawing on data from a nationally representative quantitative survey of the adult population, the article examines the prevailing concept of collaboration in public opinion and the relevance of collaboration-related issues for various groups in society. Both the general concept and the criteria for evaluating specific cases of ‘collaboration’ with the Soviet and Nazi regimes are discussed, along with assessments of the forms of (non-)memorialisation of collaboration. The dominant concept of collaboration prevailing in public opinion is relatively clear, and the boundaries of its core criteria (such as links to repression or the repressive apparatus, and work in political-administrative institutions that had real decision-making power) are strict and unambiguous. Greater ambiguity emerges when assessing specific cases of ‘collaboration’, work in lower-level positions with less power, spreading the ideologies of the occupation regimes, and so on. The article also examines the assessment of certain controversial cases of ‘collaboration’ in public discourse.